Aerobic Exercise Intensity Influences Hypotension Following Concurrent Exercise Sessions - Keese, F.; Farinatti, P.; Pescatello, L.; Cunha, F. A.; Monteiro, W. D. (International Journal of Sports Medicine, 2012)
The study investigated whether resistance and aerobic concurrent exercise (CE) with different intensities influenced postexercise hypotension (PEH). 21 healthy men (20.7±0.7 yr) performed 4 sessions: control [CTL 60 min of rest], and CE1, CE2, and CE3 consisting respectively of 2 sets of 6 exercises at 80% 1RM followed by 30 min of cycle ergometer exercise at 50%, 65%, and 80% of peak oxygen consumption (VO2peak). All sessions lasted approximately 60 min and began with resistance prior to aerobic sessions. Systolic (SBP) and diastolic (DBP) blood pressure (BP) were assessed at baseline and every 10 min during 120-min recovery. The magnitude of SBP decrease was similar after all CE sessions [CE1: 4.2±2.5 mmHg; CE2: 4.8±2.7 mmHg; CE3: 6.0±2.0 mmHg; p=0.06], but the PEH lasted approximately 1 h longer following CE2 and CE3 [120 min] compared to CE1 [60–70 min] (P<0.05). The magnitude of DBP decrease was slightly greater after CE3 and CE2 [2 mmHg] than after CE1 [1 mmHg] (P<0.05), being longer following CE3 [60 min] compared to CE2 and CE1 [40 min] (P<0.05). In conclusion, CE sessions combining resistance and aerobic sessions elicited PEH, especially when the intensity of the aerobic exercise was higher than 65% VO2peak.
Keywords: diastolic blood pressure; systolic blood pressure; endurance; exercise prescription; health; strength